2010
DOI: 10.1590/s0004-28032010000300015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baclofen on liquid and solid gastric emptying in rats

Abstract: -Context -Gamma-aminobutyric acid (GABA) is a potent inhibitory neurotransmitter. There is evidence that GABA B receptors located in the dorsal complex and in afferent fibers of the vagus nerve participate in the control of gastrointestinal motility. Objectives -To assess the intracerebroventricularly (ICV) and intravenously (IV) effect of baclofen, a GABA B receptor agonist, on liquid and solid gastric emptying in rats. Methods -Adult male Wistar rats weighing 250-300 g (n = 6-8 animals) were used. Gastric em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Previous reports localized GABA A and GABA B receptors on murine and human enteric neurons, and these cells are optimally positioned to receive microbial‐derived GABA signals . As reported by other groups, this receptor distribution may coordinate GABAergic regulation of intestinal motility, gastric emptying, gastric acid secretion, and transient lower esophageal sphincter relaxation . Interestingly, a recent in vitro study showed that the GABA agonist baclofen decreased DRG neuron activity by acting on GABA B receptors and inhibiting both low‐voltage activated and high‐voltage activated Ca 2+ currents .…”
Section: Discussionmentioning
confidence: 63%
“…Previous reports localized GABA A and GABA B receptors on murine and human enteric neurons, and these cells are optimally positioned to receive microbial‐derived GABA signals . As reported by other groups, this receptor distribution may coordinate GABAergic regulation of intestinal motility, gastric emptying, gastric acid secretion, and transient lower esophageal sphincter relaxation . Interestingly, a recent in vitro study showed that the GABA agonist baclofen decreased DRG neuron activity by acting on GABA B receptors and inhibiting both low‐voltage activated and high‐voltage activated Ca 2+ currents .…”
Section: Discussionmentioning
confidence: 63%
“…Steinert et al (15) reported that glutamine had no effect on antral, duodenal or pyloric pressures, or plasma cholecystokinin in healthy men, suggesting no effect on gastric emptying. On the contrary, baclofen, a GABA agonist, accelerated gastric emptying of solids but delayed emptying of liquid in 13 C-breath test in mice (16). These findings show that glutamine has differential effects on proximal and distal stomach emptying.…”
Section: Discussionmentioning
confidence: 99%